Beta-Human Chorionic Gonadotropin Producing Osteosarcoma of the Sacrum in a 26-Year-Old Woman: A Case Report and Review of the Literature - Ryan Glass; Jaya Ruth Asirvatham; Leonard Kahn; Mohamed Aziz (Hindawi Limited, 2015)
Ectopic secretion of beta-human chorionic gonadotropin is considered a poor prognostic marker in epithelial tumors. However, very few cases have been reported in sarcomas. We present the case of a 26-year-old female who presented with a metastatic osteosarcoma. She underwent usual testing prior to starting treatment and was found to have elevated levels of beta-human chorionic gonadotropin. As the patient was not pregnant, another source of beta-human chorionic gonadotropin secretion had to be considered. The tumor cells demonstrated positive staining for beta-human chorionic gonadotropin by immunohistochemistry, and serum levels of beta-human chorionic gonadotropin were used to monitor tumor progression and response to chemotherapy. We review the literature and discuss a potential role of beta-human chorionic gonadotropin in the treatment of such patients.